Are flowers vulnerable to xylem cavitation during drought?. Issue 1854 (3rd May 2017) - Zhang, Feng-Ping; Brodribb, Timothy J.
Abstract : Water stress is known to cause xylem cavitation in the leaves, roots and stems of plants, but little is known about the vulnerability of flowers to xylem damage during drought. This is an important gap in our understanding of how and when plants become damaged by water stress. Here we address fundamental questions about if and when flowers suffer cavitation damage, using a new technique of cavitation imaging to resolve the timing of cavitation in water-stressed flower petals compared with neighbouring leaves. Leaves and flowers from a sample of two herbaceous and two woody eudicots were exposed to a severe water stress while the spatial and temporal propagation of embolism through veins was recorded. Although in most cases water potentials inducing 50% embolism of herbaceous flower veins were more negative than neighbouring leaves, there was no significant difference between the average vulnerability of leaves and petals of herbaceous species. In both woody species, petals were more vulnerable to cavitation than leaves, in one case by more than 3 MPa. Early cavitation and subsequent damage of flowers in the two woody species would thus be expected to precede leaf damage during drought. Similar cavitation thresholds of flowers and leaves in the herb sample suggest that cavitation during water shortage in these species will occur simultaneously among aerial tissues. Species-specific differences in the cavitation thresholds of petals provide a new axis of variation that may explain contrasting flowering ecology among plant species.